TANGGUNG JAWAB HUKUM PRESIDEN DALAM PEMBERIAN IZIN PEMERIKSAAN PEJABAT NEGARA - M. Sabaruddin Sinapoy (Yuridika, 2012)
Basically the law enforcement authority granted to juridical constitutional judiciary and its parts. The parts in question here include, police, prosecutors, and the Judiciary, and in addition there are also other parts like, Lawyer (Advocate), Community Organization in the field of law, such as the Legal Aid Institute (LBH), and others. Therefore, in addition to the judiciary and its parts are one of the agencies that have functions in the field of law enforcement, but the agency today has a function in the field of law enforcement. This empirical fact is an institution that meant the President, which is constitutionally known that the President is a state agency that has the “authority in the field of government” expressed in Article 4 paragraph (1) of the 1945 Constitution.Keyword: Power, President, State Agency